The Effect of Interpersonal Interaction Factors on Buyers Purchase Intention in TikTok Livestreaming of Local Fashion Product - Talitha, Moza Abel; Irianty, Ira (UI Scholars Hub, 2025)
This study aims to determine the interpersonal interaction factors that influence purchase intentions of local Indonesian fashion products on TikTok live stream shopping, based on the SOR theory. The sample of this research is the audience of TikTok live stream shopping of local Indonesian fashion products, living in Jabodetabek, and aged between 18 to 34 years. There were 295 respondents and data were analyzed using PLS-SEM software. According to this study, Perceived similarity is positively related to Swift guanxi. In addition, Perceived similarity and Perceived responsiveness are positively related to Initial Trust. Swift guanxi and Initial Trust are positively related to Purchase Intention. In addition, swift guanxi has a mediating role for Perceived similarity in Purchase Intention. Finally, Initial Trust positively mediates the effects of Perceived responsiveness and Perceived similarity on Purchase Intention.